2007
DOI: 10.1111/j.1439-0434.2007.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and ex vitro Selection of Potato Plantlets for Resistance to Early Blight

Abstract: Reaction to the culture filtrate of Alternaria solani (Sorauer) was used as an indicator in an in vitro screening test to select lines with decreased field susceptibility to early blight from a population of 1000 putative mutants. Plantlets of cv. ÔDesire´e derived from irradiated callus of potato were inoculated in vitro with a culture filtrate of A. solani (Sorauer). Of the 45 lines selected and subsequently evaluated under conditions of natural infection in the greenhouse six showed lesser degrees of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Mean comparison in vitro method (Table 4) showed that in droplet method Desiree cultivar had low resistance level, however in direct method Desiree cultivar had high level the symptoms of early blight in vitro with were taken 1 -3 days after inoculation that results is a similar too described by [6]. Culture filtrate was used in in vitro condition and caused leaf necrotic, were similar to those caused by infection through spores as was described by [9,10,13].…”
Section: Disscusionmentioning
confidence: 59%
See 3 more Smart Citations
“…Mean comparison in vitro method (Table 4) showed that in droplet method Desiree cultivar had low resistance level, however in direct method Desiree cultivar had high level the symptoms of early blight in vitro with were taken 1 -3 days after inoculation that results is a similar too described by [6]. Culture filtrate was used in in vitro condition and caused leaf necrotic, were similar to those caused by infection through spores as was described by [9,10,13].…”
Section: Disscusionmentioning
confidence: 59%
“…This study was conducted using factorial based on completely randomized design (CRD) with 3 replications. The test tubes were placed for 6 -7 days in a growth chamber at 20˚C -25˚C, with a photosynthetic photon flow density of 100 µE/m/s and a day length of 16 h [10]. During in vitro assay the A. solani symptoms appear 1 -3 days until 6 days.…”
Section: In Vitro Selection By Direct Using Of Culture Filtrate Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of susceptibility or resistance exists in potato cultivars with some of these methods [20]. Evaluation of in vitro methods, e.g.…”
Section: Introductionmentioning
confidence: 99%